Functional analysis of six uncharacterised mutations in LDLR gene. (December 2019) - Gomez, Andrea; Colombo, Roberto; Pontoglio, Alessandro; Helman, Lorena; Kaeser, Luciana; Giunta, Gustavo; Parolin, Maria L.; Toscanini, Ulises; Cuniberti, Luis
Abstract: Background and aims: Familial hypercholesterolemia (FH) is a primary hyperlipemia. It is an autosomal dominant genetic disorder of lipoproteins metabolism mainly caused by mutations in the low density lipoprotein receptor gene ( LDLR) . We aimed to investigate the functional impact on the low density lipoprotein receptor (LDLR) activity of six uncharacterised variants located in the coding region of the LDLR gene, namely c.428G > T, c.640T > C, c.1708C > T, c.1736A > T, c.1981C > G and c.2114C > G (NM_000527.4) and to attempt to define their clinical status. Methods: Functional studies were carried out using site-directed mutagenesis techniques and expression of LDLR protein in vitro . Results were correlated with clinical data and in silico analyses in order to assess the physiopathological role of these variants. Results: This work provides functional information about 6 uncharacterised mutations in LDLR . Conclusions: The six variants studied here appeared to affect the LDLR function in vitro to different degrees, ranging from receptors with normal to slightly reduced activity to receptors exhibiting less than 10% of the wild-type activity. According to these studies and The American College of Medical Genetics and Genomics (ACMG) Standards and Guidelines, two variants could be classified as "Likely Benign" (p.(Ala705Gly) and p.(Leu570Phe)), three variants as "Pathogenic" (p.(Asp579Val), p.(Cys143Phe) and p.(Trp214Arg)) and one variant as "Likely Pathogenic" (p.(Pro661Ala)). Graphical abstract: Image 1 Highlights: More than 2100 mutations have been already identified in LDLR gene. The relationship between the receptor activity and mutations have not been demonstrated in all cases. Functional studies of six uncharacterised variants in LDLR are reported here. The six variants could be categorised following ACMG guidelines as Benign, Pathogenic or Likely Pathogenic. Predictive in silico algorithms were not always consistent with the results of the functional studies on LDLR .